Flower morphology of selected species of genera Kalanchoe and Bryophyllum in Nigeria - Tolulope Olutayo; Oluwabunmi Arogundade (Academia Biology)
A morphological study of the three Kalanchoe species in the subfamily Kalanchoideae of the family Crassulaceae in Nigeria was carried out. The qualitative and quantitative morphological attributes of the species were recorded with the aim of documenting and identifying the characters that can be used to delimit the species. Fresh samples of the flower of Kalanchoe crenata (Andr.) Haw, Kalanchoe lanceolata (Forsk.) Pers, and Bryophyllum pinnatum (Lam.) Oken were collected and subjected to morphological studies. Qualitative and quantitative attributes were recorded. Data gotten from quantitative attributes were subjected to least significance difference test (LSD) for mean separation and further subjected to single linkage cluster analysis (SLCA) and principal component analysis (PCA). Unifying attributes such as petals and sepals, four in number, were recorded. Attributes that can be used to delimit the species such as petal color were recorded.